The impact of crunchyroll´s service quality on its brand image in the portuguese anime streaming market - El Yadini, Sami (My University, 2025)
This study investigates the influence of Crunchyroll’s service quality dimensions on its brand image within the Portuguese anime streaming market. Identifying how service characteristics of distinct platforms influence consumer opinions will drive successful brand strategy and competitive separation in the anime market. The research analyses four essential variables, which include content quality alongside platform usability, customer support quality, and pricing/subscription model, to determine their effects on Crunchyroll's brand image perception. This research utilized a quantitative approach through structured surveys sent to Portuguese Crunchyroll user participants. The researchers used descriptive statistics, reliability analysis, and multiple regression techniques to evaluate data and verify variable relationships, as well as their significance and strength. The study shows that brand image receives a positive and significant impact from each service quality dimension, yet content quality and platform usability demonstrate the most powerful predictive capability. The main reasons users liked Crunchyroll stemmed from its localized anime selection and diverse offerings, along with its user-friendly interface. The evaluation of customer support and pricing strategies produced moderate results in comparison to the other variables. The study demonstrates that customers form positive brand associations because of affordable pricing combined with flexible plans and fair price structures. Service-based brand image evaluation of Crunchyroll results in both functional and experiential attributes that support the consistent delivery of quality services, optimized platforms, and strategic pricing within digital streaming markets. The research offers practical recommendations for streaming service providers to build brand reputation and maintain customer retention in their regional customer bases. The study provides new insights into service quality research and brand image studies in digital media services while establishing evaluation methods for consumer-brand relationships in subscription-based platforms.

Este estudo investiga a influência das dimensões de qualidade do serviço da Crunchyroll na sua imagem de marca no mercado português de streaming de anime. Com o crescimento da procura global por conteúdo de anime, compreender como as funcionalidades específicas de cada plataforma moldam a perceção do consumidor torna-se vital para o posicionamento da marca e a diferenciação competitiva. O estudo centra-se em quatro variáveis principais: qualidade do conteúdo, usabilidade da plataforma, qualidade do suporte ao cliente e modelo de preços/assinatura, examinando os respetivos impactos na perceção da imagem de marca da Crunchyroll pelos utilizadores. Foi utilizado um delineamento de investigação quantitativa, utilizando um instrumento de inquérito estruturado distribuído a uma amostra de utilizadores portugueses da Crunchyroll. Estatística descritiva, análise de fiabilidade e técnicas de regressão múltipla foram utilizadas para analisar os dados e determinar a significância e a força das relações entre as variáveis. Os resultados indicam que todas as quatro dimensões da qualidade do serviço influenciam positiva e significativamente a imagem da marca, com a qualidade do conteúdo e a usabilidade da plataforma emergindo como os preditores mais fortes. Os usuários valorizaram particularmente a oferta localizada e diversificada de animes da Crunchyroll, bem como a interface intuitiva e acessível da plataforma. Embora o suporte ao cliente e as estratégias de preços também tenham sido significativos, sua influência foi comparativamente moderada. Os resultados também revelam que a acessibilidade, a flexibilidade e a percepção de justiça nos preços contribuem significativamente para a formação de associações positivas à marca. O estudo conclui que a imagem da marca da Crunchyroll é moldada por atributos de serviço funcionais e experienciais, reforçando a importância da entrega de qualidade consistente, da otimização da plataforma e da precificação estratégica em ambientes competitivos de streaming digital. Ele fornece insights práticos para provedores de serviços de streaming que buscam aprimorar a força da marca e a fidelidade do consumidor em mercados regionais. A pesquisa contribui para a literatura sobre qualidade de serviço e imagem de marca em serviços de mídia digital e oferece uma estrutura para avaliar as relações consumidor-marca em plataformas baseadas em assinatura.
Keywords: Crunchyroll; Brand image; Usability; Customer support; Pricing; Anime streaming; Content quality